Introduksi Gen DefH9-iaaM dan DefH9-RI-iaaM ke dalam Genom Tanaman Tomat Menggunakan Vektor Agrobacterium tumefaciens - Ragapadmi S Purnamaningsih (Jurnal AgroBiogen, 2010)
Introduction of DefH9-iaaM and DefH9-RI-iaaM GeneInto Tomato Genome Using Agrobacterium tumefaciens.Ragapadmi Purnamaningsih. Plant genetic improvementcan be conducted through genetic engineering.Parthenocarpic fruit production could increase fruitproduction and its qulities. IAA genes were introduced intothree tomato cultivars Ratna, Opal and LV 6117 using twoconstract genes DefH9-iaaM and DefH9-RI-iaaM. The iaaMgene is able to increase auxin biosynthesis in transgenicplant cells and organs because indol-eacetamide,synthesized by the product of the iaaM gene, is convertedeither chemically or enzimatically to indole-3-acetic acid(IAA), while the promotor DefH9 enable IAA gene expressedspecifically in the ovules. The objectives of this experimentwas to identify gene introduction into plant genom of threetomato cultivars. The factors tested were two constract ofIAA genes (DefH9-iaaM or DefH9-RI-iaaM), tomato cultivars(Ratna, Opal, and LV 6117) and time of explant inoculation(5, 15, 30 minute). The result showed that the best timeinoculation was 5 minute. Otherwise three tomato cultivarsresponse better to DefH9-RI-iaaM than DefH9-iaaM. The totalefficiency of regeneration and total efficiency oftransformation of both genes were 25.38% and 20.32%. PCRanalysis showed that 10 plant have positive PCR, were 1plant carried (Opal) DefH9-iaaM gene and 9 plant (Ratna,Opal, LV 6117) carried DefH9-RI-iaaM gene.